A Review of Motor Innervation in Growing Meat Animals - Swatland, Howard J. (European Journal of Applied Sciences, 2024)
Meat animals have been bred to have enormous muscles. The genes regulating myogenesis and muscle growth are now becoming known. How does the motor innervation interact with massive increases in myofibre diameters and numbers? Stress‑susceptible pigs have myofibres with a ryanodine mutation in their calcium ion release channels. This leads to excessive muscle activation and the hypertrophy of fast-contracting myofibres. These myofibres develop large neuromuscular junctions, often with extra axonal sprouts and double motor end plates. Mutations in the myostatin gene cause myofibre hyperplasia in double muscled cattle. Terminal axons have increased branching to innervate the extra myofibres. The number of neuromuscular spindles to give feedback to the cerebellum is increased and spindles have more intrafusal myofibres regulating feedback. Is the motor innervation merely responding to the increased muscle mass, or is this an interactive system?